Pengaruh Teknik Bernyanyi dan Permainan Kartu Bergambar Terhadap Sikap dan Perilaku Gizi Pada Anak Taman Kanak-Kanak - Eri Virmando; Sapja Anantanyu; Kusnandar Kusnandar (Media Kesehatan Masyarakat Indonesia, 2018)
Nutrition education in kindergarten children is an effort to increase awareness of healthy living behaviorin consumption of fruits and vegetables through Communication, Information, and Education (CIE). This studyaims to analyze the effect of nutritional education through the technique of singing and picture card games to theattitudes and nutritional behavior of kindergarten children. The design in this study was quasi-experimental, withpre-post test design with control group design. The subjects of this study were 68 students from 4 kindergartenschools in Tempilang Subdistrict, this study was conducted in January - March 2018. Nutrition education used wasa technique of singing, card game, and joint intervention. The results show that there are differences in nutritionalattitudes and behaviors in nutritional education. The combined intervention has the highest score on the attitudesand nutritional behavior of 7.38 ± 0.98 and 49.06 is significantly different from other intervention media. Therewas a change of good nutrition that increased after intervention (97,1%) from before intervention (95,6%) andchange of good nutrition behavior that increased after intervention (45,6%) before intervention (79,4%). Nutritioneducation through joint intervention provides a change in the improvement of nutritional attitudes and behaviorsin child kindergartens.